Container Survey of Mosquito Breeding Sites in a University Campus in Kuala Lumpur, Malaysia - Chen, C.D.; Lee, H.L.; Stella-Wong, S.P.; Lau, K.W.; Sofian-Azirun, Mohd (2009)
A survey on container breeding sites of Aedes spp. and Culex spp. larvae was conducted in the campus of the University of Malaya, Kuala Lumpur. Sampling was carried out by dipping using pipette or dipper depending on container types. All breeding sources of mosquito larvae were grouped into eight different container types: plastic container, plastic pail, bottle, earthen plate, natural container, vase, can and concrete tank. A total of 262 containers were identified as potential breeding sites. However, only 65 containers (86.15 outdoors and 13.85 indoors) were found containing larvae. Among all types of containers, 50.00 of the total surveyed natural containers were positive with mosquito larvae, followed by plastic containers (32.77), plastic pails (23.81), concrete tanks (20.00), vases (18.75), bottles (14.71), cans (13.33) and earthen plates (11.90). The collected mosquito larvae were those of Aedes albopictus (86.96), Aedes niveus group (5.80) and Culex quinquefasciatus (7.24). No Aedes aegypti was found in any container in the study site. This study indicated that Ae. albopictus was capable of breeding in a wide range of container types. To control these mosquitoes, the elimination of artificial and natural containers or alteration of breeding sites in and around the campus areas should be taken into consideration. Towards this goal, the university management should practise Integrated Vector Management (IVM) in the campus.